Félix: a Late Pleistocene White Whale (Delphinapterus Leucas) Skeleton From Champlain Sea Deposits at Saint-Félix-de-Valois, Québec - Harington, C.; Lebel, Serge; Paiement, Maxime; de Vernal, Anne (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractA nearly complete, articulated skeleton of an old white whale (Delphinapterus leucas) from Champlain Sea deposits at Saint-Félix-de-Valois is the best preserved specimen of its kind recorded from North America. It is one of 21 white whale specimens known from Champlain Sea deposits. Collagen from a vertebra yielded an accelerator mass spectrometry radiocarbon date of 10 700 ± 90 BP, which, with stratigraphic and paleoenvironmental data, is in accord with our knowledge of the past distribution of this species, its known habitat and habits. This study quantitatively traces regional sea-surface temperature, salinity and ice-cover. Dinocysts indicate a change from cold to cool conditions in surface water during that period corresponding to the withdrawal of ice and the beginning of the Holocene.